Hubungan Sanitasi Lingkungan dengan Kejadian Stunting pada Balita di Desa Aikmel, Kabupaten Lombok Timur - Ghazi Fathurrahman Alfarizi; Rayyan Dzakwan Prasetya (Journal of Applied Health Sciences, 2026)
Stunting remains a major public health problem in Indonesia, particularly in areas with inadequate environmental sanitation. This study aims to analyze the relationship between environmental sanitation and the incidence of stunting among children under five in Aikmel Village, East Lombok Regency. This research employed an analytical observational design with a cross-sectional approach. The sample consisted of children aged 0–59 months selected using simple random sampling. Data were collected through anthropometric measurements, environmental sanitation observations, and structured interviews using questionnaires. Data analysis was conducted using univariate analysis, bivariate analysis with chi-square tests, and multivariate analysis with logistic regression. The results showed a significant relationship between environmental sanitation and stunting incidence (p < 0.05). Variables such as access to clean water, availability of latrines, and hygiene practices had significant effects on stunting. Children living in households with poor sanitation were more likely to experience stunting compared to those in households with adequate sanitation. Multivariate analysis indicated that access to clean water and latrine ownership were the most dominant factors influencing stunting. In conclusion, environmental sanitation is a key determinant of stunting. Efforts to prevent stunting should involve integrated interventions, including improving access to clean water, providing adequate sanitation facilities, and promoting healthy hygiene practices. The findings of this study are expected to contribute to evidence-based public health policy development for more effective stunting reduction programs.